Pengembangan Media Pembelajaran dalam Bentuk Buku Saku Digital Berbasis Android Materi Ajar Gerak dan Gaya di SMK 1 Kedungwuni - Reza, M. Fahrudin Ali; Purwanti, Dwi (Edu Komputika Journal, 2017)
This study aims to determine how to develop Android-based instructional media in teaching materials and apply motion and force the application into learning in school as an alternative to learning. Application development method used is the waterfall which has a cycle stages of requirements analysis, design, implementation (application development) and testing phases. The testing phase consists of blackbox testing, validation software (learning media applications) and test stages of user feedback through a questionnaire data retrieval. Analysis of the data using a Likert scale to determine the length of the interval for the application of learning media assessment. The test results showed that the learning media in the form of Android-based digital pocket book category fit for use as an alternative learning at school and outside of school. Product validation testing media applications obtained a score of 69 with a percentage of 75% intervals media ratings (criteria of Agree / Worth). While the test results obtained by user feedback score of 1967 with a percentage interval feasibility assessment of media that is 80.87% (the criteria of Agree / Worth).